Towards Facile Radiolabeling and Preparation of Gallium-68-/Bismuth-213-DOTA-[Thi8, Met(O2)11]-Substance P for Future Clinical Application: First Experiences - Janine Suthiram; Thomas Ebenhan; Biljana Marjanovic-Painter; Mike M. Sathekge; Jan Rijn Zeevaart (MDPI AG, 2021)
Substance P (SP) is a small peptide commonly known as a preferential endogenous ligand for the transmembrane neurokinin-1 receptor. Nuclear Medicine procedures currently involve radiolabeled SP derivatives in peptide radioligand endotherapy of inoperable glioblastoma. Promising clinical results sparked the demand for facile production strategies for a functionalized 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid-[Thi8, Met(O2)11]-SP to allow for rapid Gallium-68 or Bismuth-213 complexation. Therefore, we provide a simple kit-like radiotracer preparation method that caters for the gallium-68 activity eluted from a SnO2 generator matrix as well as preliminary results on the adaptability to produce [213Bi]Bi-DOTA-[Thi8, Met(O2)11]SP from the same vials containing the same starting material. Following a phase of radioanalysis for complexation of gallium-68 to DOTA-[Thi8, Met(O2)11]SP and assessing the radiolabeling parameters, the vials containing appropriate kit-prototype material were produced in freeze-dried batches. The facile radiolabeling performance was tested and parameters for future human application were calculated to meet the criteria for theranostic loco-regional co-administration of activity doses comprising [68Ga]Ga-DOTA-[Thi8, Met(O2)11]SP mixed with [213Bi]Bi-DOTA-[Thi8, Met(O2)11]SP. [68Ga]Ga-DOTA-[Thi8, Met(O2)11]SP was prepared quantitatively from lyophilized starting material within 25 min providing the required molar activity (18 ± 4 GBq/µmol) and activity concentration (98 ± 24 MBq/mL), radiochemical purity (>95%) and sustained radiolabeling performance (4 months at >95% LE) as well as acceptable product quality (>95% for 120 min). Additionally, vials of the same starting materials were successfully adapted to a labeling strategy available for preparation of [213Bi]Bi-DOTA-[Thi8, Met(O2)11]SP providing sufficient activity for 1-2 human doses. The resultant formulation of [68Ga]Ga-/[213Bi]Bi-DOTA-[Thi8, Met(O2)11]SP activity doses was considered of adequate radiochemical quality for administration. This investigation proposes a simple kit-like formulation of DOTA-[Thi8, Met(O2)11]SP-a first-line investigation into a user friendly, straightforward tracer preparation that would warrant efficient clinical investigations in the future. Quantitative radiolabeling was accomplished for [68Ga]Ga-DOTA-[Thi8, Met(O2)11]SP and [213Bi]Bi-DOTA-[Thi8, Met(O2)11]SP preparations; a key requirement when addressing the specific route of catheter-assisted co-injection directly into the intratumoral cavities.